Identification of the Novel Tumor Suppressor Role of FOCAD/miR-491-5p to Inhibit Cancer Stemness, Drug Resistance and Metastasis via Regulating RABIF/MMP Signaling in Triple Negative Breast Cancer - Wei-Chieh Huang; Hsiang-Cheng Chi; Shiao-Lin Tung; Po-Ming Chen; Ya-Chi Shih; Yi-Ching Huang; Pei-Yi Chu (Cells)
Triple negative breast cancer (TNBC) possesses poor prognosis mainly due to development of chemoresistance and lack of effective endocrine or targeted therapies. MiR-491-5p has been found to play a tumor suppressor role in many cancers including breast cancer. However, the precise role of miR-491-5p in TNBC has never been elucidated. In this study, we reported the novel tumor suppressor function of FOCAD/miR-491-5p in TNBC. High expression of miR-491-5p was found to be associated with better overall survival in breast cancer patients. We found that miR-491-5p could be an intronic microRNA processed form FOCAD gene. We are the first to demonstrate that both miR-491-5p and FOCAD function as tumor suppressors to inhibit cancer stemness, epithelial-mesenchymal transition, drug resistance, cell migration/invasion, and pulmonary metastasis etc. in TNBC. MiR-491-5p was first reported to directly target Rab interacting factor (RABIF) to downregulate RABIF-mediated TNBC cancer stemness, drug resistance, cell invasion, and pulmonary metastasis via matrix metalloproteinase (MMP) signaling. High expression of RABIF was found to be correlated with poor clinical outcomes of breast cancer and TNBC patients. Our data indicated that miR-491-5p and RABIF are potential prognostic biomarkers and targeting the novel FOCAD/miR-491-5p/RABIF/MMP signaling pathway could serve as a promising strategy in TNBC treatment.